Embryonic development, hatching time and newborn juveniles of Octopus tehuelchus under two culture temperatures - Braga, Ramiro (2021)
The development of cephalopods early life stages is strongly influenced by environmental variables, especially temperature. Octopus tehuelchus (d'Orbigny, 1834) is an Atlantic Patagonian fishery resource currently being studied as a new species for cultivation; however it is not known how temperature modulates its early life stages. In this work, egg masses were artificially incubated at 13 and 16 °C under controlled aquarium conditions. In each thermal treatment, the stages of embryonic development, embryo morphometry and survival throughout embryogenesis, as well as embryogenesis duration were recorded. After hatching, the morphological description of the juveniles was achieved and survival time in starvation was calculated for both temperatures. At 16 °C the mean embryonic duration was 85 days shorter than at 13 °C. For both thermal treatments, the highest mortalities occurred up to the beginning of organogenesis, and no significant differences in hatching success were observed. The temperature also showed the potential to increase or decrease the juvenile performance at the early post hatching period. This resulted in a significant reduction in size and weight of new born juveniles at 13 °C but also in an average increment of 7 days in their survival in starvation when compared to octopus reared at 16 °C. The chromatophore pattern was similar for both thermal treatments and was characteristic of juveniles of this species. The observed differences seem to show adaptive mechanisms that optimize embryos and juveniles viability under the different environmental temperatures that can be found in the northern Atlantic Patagonian coast. From a practical point of view, our findings are important to define the biological parameters and associated procedures for the cultivation of the early life stages of O. tehuelchus.